Model considerations on physico-chemical nature of protein-nucleic acid contacts through amino acid carboxylic groups: spectroscopic data - Samijlenko, S.P.; Kolomiets, I.M.; Kondratyuk, I.V.; Stepanyugin, A.V. (Биополимеры и клетка, 1998)
This paper generalizes the results of a series of the works on spectroscopic (IR, UV, NMR, Roman) investigations of complexes of nucleotide bases, their numerous methyl and glycosyl derivatives with amino acid carboxylic groups modeling point protein-nucleic acid contacts. The specificity of interactions between bases and two forms of carboxylic group – neutral and deprotonated – was determined. The structures of the complexes investigated were established, and the role of various atomic groups in their formation was elucidated as welt. Special consideration has been given to the frequent occurrence of proton transfer in the studied complexes. The significance of the data obtained in understanding of elementary mechanisms of protein-nucleic acid interactions is discussed. Узагальнено результати серії робіт спектроскопічного (ІЧ, УФ, ЯМР, Раман) дослідження комплексів нуклеотидних основ та їхніх численних метил- та глікозилпохідних з карбоксильною групою амінокислот, що моделюють точкові білково-нуклеїнові контакти. Встановлено специфічність взаємодії основ з двома формами карбоксильної групи – нейтральною та депротонованою. Визначено структуру досліджуваних комплексів, а також з'ясовано роль різних атомних груп основ у їхньому формуванні. Особливу увагу привертає поширеність явища перенесення протона в досліджених комплексах. Обговорюється значення отриманих результатів для розуміння елементарних механізмів білково-нуклеїнових взаємодій. Обобщены результаты серии спектроскопического (ИК, УФ, ЯМР, Раман) исследования комплексов нуклеотидных оснований и их многочисленных метил- и гликозилпроизводных с карбоксильной группой аминокислот, моделирующих точечные белково-нуклеиновые контакты. Установлена специфичность взаимодействия оснований с двумя формами карбоксильной группы. Определена структура исследованных комплексов, а также выяснена роль разных атомных групп оснований в их образовании. Особое внимание обращает на себя распространенность явления переноса протона в исследованных комплексах. Обсуждается значение полученных результатов для понимания элементарных механизмов белково-нуклеиновых взаимодействий.